Diagnosing and Managing LADA: A Review of the Overlooked Diabetes Subtype - Wojszczyk, Maciej; Kulbacka, Julia; Dziedzic, Karol; Arczewski, Filip; Wójcikiewicz, Michalina; Chuncia-Ileczko, Marta; Kacperczyk, Julia; Czyż, Witold; Pasek, Piotr; Ryniecka, Julia (Quality in Sport, 2025)
LADA (latent autoimmune diabetes in adults) is a dual form of diabetes, combining the autoimmune features typical of type 1 diabetes and the clinical and metabolic aspects of type 2 diabetes. Due to the slow development of symptoms and often late age of onset, LADA is frequently misdiagnosed as type 2 diabetes, which can lead to a delay in appropriate treatment. It is estimated that LADA affects between 4% and 12% of adults initially diagnosed with type 2 diabetes, making it a more common disease entity than previously thought. This paper examines current data on the epidemiology, pathogenesis, genetic factors and diagnostic criteria of LADA. Particular attention was given to the immunological and genetic aspects of the disease, which allow a more accurate differentiation of LADA from type 2 diabetes. The review also discusses the significance of early insulin therapy aimed at beta-cell preservation and the role of alternative treatments, such as DPP-4 inhibitors, which may influence disease progression. Diagnostic and therapeutic challenges stemming from the phenotypic similarities between LADA and type 2 diabetes are highlighted, along with potential benefits of early detection.